The Perlecan Fragment LG3 Regulates Homing of Mesenchymal Stem Cells and Neointima Formation During Vascular Rejection. Issue 5 (23rd March 2015) - Pilon, E. A.; Dieudé, M.; Qi, S.; Hamelin, K.; Pomerleau, L.; Beillevaire, D.; Durocher, Y.; Zutter, M.; Coutu, D.; Perreault, C.; Hébert, M. J.
Abstract : Transplant vasculopathy is associated with neointimal accumulation of recipient‐derived mesenchymal stem cells. Increased circulating levels of LG3, a C‐terminal fragment of perlecan, were found in renal transplant patients with vascular rejection. Here, we evaluated whether LG3 regulates the migration and homing of mesenchymal stem cells and the accumulation of recipient‐derived neointimal cells. Mice were transplanted with a fully‐MHC mismatched aortic graft followed by intravenous injection of recombinant LG3. LG3 injections increased neointimal accumulation of α‐smooth muscle actin positive cells. When green fluorescent protein (GFP)‐transgenic mice were used as recipients, LG3 injection favored accumulation of GFP+ cells to sites of neointima formation. LG3 increased horizontal migration and transmigration of mouse and human MSC in vitro and led to increased ERK1/2 phosphorylation. Neutralizing β1 integrin antibodies or use of mesenchymal stem cells from α2 integrin−/− mice decreased migration in response to recombinant LG3. Reduced intima‐media ratios and decreased numbers of neointimal cells showing ERK1/2 phosphorylation were found in α2−/− recipients injected with recombinant LG3. Collectively, our results suggest that LG3, through interactions with α2β1 integrins on recipient‐derived cells leading to activation of ERK1/2 and increased migration, favors myointimal thickening. Abstract : The perlecan fragment LG3 enhances migration of mesenchymal stem cells and allograft vascular remodeling.